Ethical Policy and The Modernization of Gemeente Cirebon (1901–1930) - Prapanji Galih Wicaksono; Muhammad Fajar Meishfar; Safira Nur Afifah (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2026)
This study examines the implementation of the Ethical Policy and the formation of colonial modernity in Gemeente Cirebon between 1901 and 1930, with particular attention to transportation infrastructure and its social consequences. Using the historical method and a descriptive qualitative approach, the study analyzes colonial reports, statistical records, administrative archives, contemporary newspapers, and relevant secondary literature. The findings show that railways, roads, and port facilities expanded regional connectivity and accelerated the circulation of export commodities, especially sugar, from inland production areas to the Port of Cirebon. Yet this modernization was deeply ambivalent. While it stimulated urban growth, economic circulation, and access to modern facilities, it also sharpened social inequality and strengthened colonial control over indigenous communities. Improvements in the economic, health, and educational sectors were distributed unevenly and remained closely tied to colonial interests. The article argues that the Ethical Policy in Cirebon functioned not only as a reform program but also as an instrument of exploitation, regulation, and social control.